Bibliometric analysis of the quality of higher education in Chile - Araya-Pizarro, Sebastián (2023)
The study aimed to analyze the scientific production on the quality of higher education in Chile. A descriptive longitudinal bibliometric review was carried out on articles published in the Scopus database between 2011 and 2021. The articles were classified according to the thematic classification algorithm of Callon et al. (1999). A total of 59 articles were identified, largely published in Latin American journals, and written collaboratively by researchers affiliated with specific institutions. Five important thematic clusters were identified, consisting of two basic, two drivers, and one emerging cluster. The study concludes that the quality of higher education is a relevant research topic in Chile with increasing productivity but high concentration, mainly explored from the perspective of institutional accreditation and quality assurance.